2018
DOI: 10.4081/or.2018.7541
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison between titanium and cobalt chromium rods used in a pedicle subtraction osteotomy model

Abstract: Instrumentation failure is a common complication following complex spinal reconstruction and deformity correction. Rod fracture is the most frequent mode of hardware failure and often occurs at or near a 3-column osteotomy site. Titanium (Ti) rods are commonly utilized for spinal fixations, however, theoretically stiffer materials, such as cobalt-chrome (CoCr) rods are also available. Despite ongoing use in clinical practice, there is little biomechanical evidence that compares the construct ability to withsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…These studies reported the different outcomes of interest concerning our study questions. Four studies compared correction rate [ 12 , 16 , 19 , 20 ]; five studies compared rod fracture [ 17 19 , 24 , 25 ]; three studies compared thoracic kyphosis [ 12 , 16 , 20 ], proximal junctional kyphosis [ 12 , 17 , 18 ], and fatigue life [ 21 23 ] each; two studies compared lumbar lordosis [ 12 , 16 ] and bending stiffness [ 22 , 23 ] each. Studies comparing similar outcomes were analyzed together in the same forest plot.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies reported the different outcomes of interest concerning our study questions. Four studies compared correction rate [ 12 , 16 , 19 , 20 ]; five studies compared rod fracture [ 17 19 , 24 , 25 ]; three studies compared thoracic kyphosis [ 12 , 16 , 20 ], proximal junctional kyphosis [ 12 , 17 , 18 ], and fatigue life [ 21 23 ] each; two studies compared lumbar lordosis [ 12 , 16 ] and bending stiffness [ 22 , 23 ] each. Studies comparing similar outcomes were analyzed together in the same forest plot.…”
Section: Resultsmentioning
confidence: 99%
“…While at the review level, the risk of biases was identified as some studies had our data of interest to be extracted; other studies need calculation to obtain the required data for analysis. The overall mean age of participants in two groups could not be calculated as median was used rather than mean in some studies [ 20 ] and not reported in some studies [ 21 24 ]. Also, the overall follow-up time could not be calculated as data were not reported in some studies [ 20 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies evaluating rod breaking strength 7,13 have shown that cobalt chromium rods withstand around three to five more stress cycles than titanium alloy rods and support a higher load up to breakage. In addition, they showed that larger diameter rods are more resistant.…”
Section: Discussionmentioning
confidence: 99%